Carbonate chemistry from a long-term (12-months) multiple driver aquarium experiment with the cold-water coral Desmophyllum pertusum - Kristina K Beck; J Murray Roberts; Zoe Burns; Blair Easton; Sarah Kaye; Marta Peña Fernández; Uwe Wolfram; Sebastian Hennige (PANGAEA, 2025)
We conducted a long-term (12 months) multiple driver aquarium experiment under future environmental conditions at St Abbs Marine Station (UK) with the cold-water coral Lophelia pertusa (syn. Desmophyllum pertusum) sampled from Tisler Reef (Skagerrak). The experiment consisted of four different treatments to investigate the combined effect of ocean acidification, warming, deoxygenation and food limitation on their physiology: 1) control (9 °C, pH 8.1, 100 % oxygen, 100 % food availability), 2) multiple stressor with high feeding (HF; 12 °C, pH 7.7, 90 % oxygen, 100 % food availability), 3) multiple stressor with low feeding (LF; 12 °C, pH 7.7, 90 % oxygen, 50 % food availability) and 4) reduced oxygen (9 °C, pH 8.1, 90 % oxygen, 100 % food availability). Every treatment consisted of three replicate tanks with four live corals (12 in total). Water parameters (temperature, salinity, pH and oxygen concentration) were measured five times per week in every coral tank. Total alkalinity (TA) samples were taken from every coral tank biweekly in order to determine the whole carbonate system using the programme CO2SYS (Pierrot et al., 2006) to calculate carbonate chemistry from measured TA and pHT according to Hoppe et al. (2012) with the dissociation constants of carbonic acid in seawater (K1 and K2) from Lueker et al. (2000), the dissociation constants of hydrogen sulphate from Dickson (1990) and boric acid from Uppström (1974) and pHT.